2006
DOI: 10.1111/j.1744-7909.2006.00246.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of theGrifola frondosaTrehalose Synthase Gene and Improvement of Drought‐Tolerance in Sugarcane(Saccharum officinarumL.)

Abstract: Trehalose is a nonreducing disaccharide of glucose that functions as a protectant in the stabilization of biological structures and enhances stress tolerance to abiotic stresses in organisms. We report here the expression of a Grifola frondosa trehalose synthase (TSase) gene for improving drought tolerance in sugarcane (Saccharum officinarum L.). The expression of the transgene was under the control of two tandem copies of the CaMV35S promoter and transferred into sugarcane by Agrobacterium tumefaciens EHA105.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
6

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 30 publications
2
52
0
6
Order By: Relevance
“…El-Bashiti et al (2005) showed that trehalose may play a role as an osmoprotectant compound in wheat species under salt and drought stress conditions. Zhang et al (2006) demonstrated that transgenic sugarcane transformed with the Grifola frondosa trehalose synthase (TSase) gene accumulated high levels of trehalose and showed enhanced tolerance to drought. In another experiment, Li et al (2011) showed that in rice, the overexpression of trehalose-6-phosphate synthase enhanced the abiotic stress tolerance of plants by increasing the amount of trehalose and proline, as well as regulating the expression of some stress-related genes.…”
Section: Discussionmentioning
confidence: 99%
“…El-Bashiti et al (2005) showed that trehalose may play a role as an osmoprotectant compound in wheat species under salt and drought stress conditions. Zhang et al (2006) demonstrated that transgenic sugarcane transformed with the Grifola frondosa trehalose synthase (TSase) gene accumulated high levels of trehalose and showed enhanced tolerance to drought. In another experiment, Li et al (2011) showed that in rice, the overexpression of trehalose-6-phosphate synthase enhanced the abiotic stress tolerance of plants by increasing the amount of trehalose and proline, as well as regulating the expression of some stress-related genes.…”
Section: Discussionmentioning
confidence: 99%
“…According to Chary et al [21], the AtTPS6 gene (class II) from Arabidopsis, is important in the control of cellular morphogenesis because it fully complements mutants with defects in the cell shape (csp-1). Sugarcane plants (Saccharum officinarum L.), encoding a mushroom TPS gene (Grifola frondosa) showed enhanced water stress tolerance and high productivity in drought conditions [22]. Nowadays sugarcane can be considered as one of the most important crops in the world; Brazil produced more then 620 million tons in 2010/2011 harvest (http://www.portalunica.com.br).…”
mentioning
confidence: 99%
“…While the nontransformed plants began turning yellow at the third day, with wilting and drying extending from old leaves to young leaves in seven days, all transgenic plants kept green and began turning yellow only at the seventh day, indicating their improvement regarding osmotic stress tolerance. Zhang et al (2006) carried out a similar approach using the same gene in sugarcane, generating transgenic plants that accumulated high levels of trehalose www.intechopen.com (up to 8.805-12.863 mg/g fresh weight), whereas trehalose was undetectable in nontransgenic plants. Trehalose accumulation in these plants resulted in increased drought tolerance, as shown by the drought physiological indexes, such as the rate of bound water/free water, plasma membrane permeability, malondialdehyde content, chlorophyll a and b contents, and activity of SOD and POD of the excised leaves.…”
Section: Trehalosementioning
confidence: 99%